Mappasanra: Praktik Gadai Sawah di Desa Bulutellue, Kabupaten Sinjai - Abdul Rahman (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to determine the process of rice field pawning in Bulutellue Village, District of Sinjai Regency while analyzing the causes of rice field pawning. The type of research used is a qualitative descriptive research method that observes by interacting with the main informants, namely pawners because they are the actors in the implementation of Rice Field Pawning and pawn recipients in Bulutellue Village. Data collection techniques used are observation, interviews, and documentation. The data obtained are then processed using data analysis techniques in the form of data reduction, data presentation and conclusion drawing. And also data validation using Member Check. The results of this study indicate that Rice Field Pawning in Bulutellue Village was initially a pawn in the form of a garden then over time changed into a rice field pawning and this has become a tradition. This rice field pawning process can also be used to cover up shame or siri' and this rice field pawning process has some that have verbal agreements and some also have written agreements. There is also one of the customary laws that still applies today and is used as a tradition by the people in Bulutellue Village. The factors causing the occurrence of rice field mortgages in Bulutellue Village are economic factors, for example those related to weddings and education.